Implementation of Family Nursing Care on the Level of Family Independence in Overcoming Family Health Problems - Agustini, Ni Rai Sintya; Solehah, Eka Lutfiatus; Lestarini, Putu Ayu (Journal of Language and Health, 2024)
The family, as the smallest social unit, is interdependent and crucial in addressing health issues collectively. Family nursing care involves transferring knowledge and skills to enable families to independently manage health problems, aiming to foster behavioral change toward better health practices. This study investigates the impact of family nursing care on the level of family independence in managing health issues in Banjar Kesambi, Kerobokan. Using a quasi-experimental one-group pretest-posttest design, 60 families meeting specific criteria were selected through purposive sampling. Data were analyzed using univariate and bivariate (dependent T-test) methods. Results indicated a significant positive effect of family nursing care on family independence in managing health challenges (p-value = 0.000).